Membangun Generasi Bijak, Cerdas, Santun pada Era Digitalisasi melalui Edukasi Etika Digital bagi Remaja Sekolah Menengah Pertama - Melisa Arisanty; Yasir Riady; Selly Anastassia Amellia Kharis; Anton Robiansyah; Sri Sukatmi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
The issue of digital ethics is a major problem that needs to be resolved. The challenge of implementing digital ethics amidst increasingly rapid technological developments is the main focus in various digital education and literacy activities. Digital Education and Literacy are the main keys to handling problems related to digital ethics, such as the spread of hoaxes, cyberbullying, Hatescpeech and Hatecomment, war flaming, fraud, SARA violations, distribution of content containing violence and pornography and so on. Therefore, community service activities regarding digital ethics education for junior high school teenagers at SMP PGRI 1 Ciputat can have the opportunity to increase teenagers' awareness of implementing digital ethics when utilizing various digital media platforms. The focus of this community service activity is teenagers, especially junior high school (SMP) teenagers, because it is considered the initial phase in the formation of identity and self. The formation of behavior as an adult also depends on what kind of moral education was given as a teenager. Based on the evaluation, this educational activity about digital ethics is very useful and able to increase awareness among teenagers, especially at SMP PGRI 1 Ciputat, about the importance of applying digital ethics in their daily activities when accessing digital media.